Determinants of Acidobacteria activity inferred from the relative abundances of 16S rRNA transcripts in German grassland and forest soils. (26th June 2013) - Foesel, Bärbel U.; Nägele, Verena; Naether, Astrid; Wüst, Pia K.; Weinert, Jan; Bonkowski, Michael; Lohaus, Gertrud; Polle, Andrea; Alt, Fabian; Oelmann, Yvonne; Fischer, Markus; Friedrich, Michael W.; et al.
Summary 16S rRNA genes and transcripts of Acidobacteria were investigated in 57 grassland and forest soils of three different geographic regions. Acidobacteria contributed 9–31% of bacterial 16S rRNA genes whereas the relative abundances of the respective transcripts were 4–16%. The specific cellular 16S rRNA content (determined as molar ratio of rRNA : rRNA genes) ranged between 3 and 80, indicating a low in situ growth rate. Correlations with flagellate numbers, vascular plant diversity and soil respiration suggest that biotic interactions are important determinants of Acidobacteria 16S rRNA transcript abundances in soils. While the phylogenetic composition of Acidobacteria differed significantly between grassland and forest soils, high throughput denaturing gradient gel electrophoresis and terminal restriction fragment length polymorphism fingerprinting detected 16S rRNA transcripts of most phylotypes in situ. Partial least squares regression suggested that chemical soil conditions such as pH, total nitrogen, C : N ratio, ammonia concentrations and total phosphorus affect the composition of this active fraction of Acidobacteria. Transcript abundance for individual Acidobacteria phylotypes was found to correlate with particular physicochemical (pH, temperature, nitrogen or phosphorus) and, most notably, biological parameters (respiration rates, abundances of ciliates or amoebae, vascular plant diversity), providing culture‐independent evidence for a distinct niche specialization of different Acidobacteria even from the same subdivision.